Neutrophil depletion in the pre-implantation phase impairs pregnancy index, placenta and fetus development - Hebeda, Cristina Bichels; Savioli, Anna Carolina; Scharf, Pablo; de Paula-Silva, Marina; Gil, Cristiane Damas; Farsky, Sandra Helena Poliselli; Sandri, Silvana (Frontiers in Immunology, 2022)
Maternal neutrophils are relevant players in gestational tolerance and fetus delivery. Nonetheless, their links in each phase of the pregnancy are unknown. We here investigated the role of maternal neutrophils during the blastocyst implantation and outcomes on the pregnancy index, placenta, and fetus development. Neutrophils were pharmacologically depleted by i.p. injection of anti-Gr1 (anti-neutrophils; 200 µg) 24 hours after plug visualization in allogeneic mated C57Bl6/BALB/c mice. Depletion of peripheral neutrophil lasted until 48 hours after anti-Gr1 injection (day 1-3). On day 5.5 of gestation, neutrophil depletion impaired the blastocyst implantation, as 50% of pregnant mice presented reduced implantation sites. On day 18.5 neutrophil depletion reduced the pregnancy rate and index (40% of pregnancy success), altered uterine horns' disposition, and modified the structure of the placenta. Reduced junctional zone, associated with decreased numbers of giant trophoblasts, spongiotrophoblast, and cells labeled for vascular endothelial growth factor (VEGF); platelet-endothelial cell adhesion molecule (PECAM-1), and intercellular cell adhesion molecule (ICAM-1), important markers of angiogenesis and adhesiveness, were detected. Furthermore, neutrophil depletion caused higher frequency of monocytes, natural killers and T regulatory cells, and lower frequency of cytotoxic T cells in the blood, and abnormal development of offspring. Associated, data here highlight the pivotal role of neutrophils actions in the preimplantation period on pregnancy outcomes, and address further investigations on the imbricating signaling evoked by neutrophils in the trophoblastic interaction between uterine epithelium.